Comprehensive assessment and intervention strategies of urban light pollution in China based on AHP and entropy weight method - Chen, Yiying (Transactions on Environment, Energy and Earth Sciences, 2024)
Rapid economic growth and urbanization have exacerbated light pollution, threatening ecosystems and human health. This study develops a robust evaluation system using the entropy weight method and analytic hierarchy process (AHP), ensuring objective index weighting and reliable results. By incorporating precise data such as the night light index (DN value), it provides a more accurate assessment of light pollution. The research identifies a decreasing trend in light pollution from major to smaller cities, highlighting the correlation with urban development levels. Based on these findings, the study recommends targeted strategies: promoting green lighting, optimizing urban planning, and enhancing light pollution prevention facilities. These measures aim to mitigate light pollution's impact, protecting human health and ecological balance. Effectively managing light pollution requires collaborative efforts from government, businesses, communities, and the public to create a healthier nocturnal environment.